Investigation of physico chemical, mechanical and thermal properties of the Guettarda speciosa bark fibers. (2021) - Solai Senthi Kumar, K.; Vivekananthan, M.; Saravanakumar, M.; Steephun Raj, F.
Abstract: The material production by using synthetic fibers is a strong contributor to carbon emissions and waste. While in growing environmental consciousness. Instist of the synthetic fibers the natural fibers act as a substitute due to their renewable, eco-friendly and bio-degradable nature. Natural cellulose fibers are newly identified from the sources of Guettarda speciosa fibers (ALF). This study is intended to understand the characteristics of ALF extracted from the bark of the Guettarda speciosa and its physicochemical properties. The fibers structures was analyzed by FT-IR and X-ray diffraction. Cellulose content are (72.59 wt%), density (905 kg/m 3 ), and crystalline index (52.99%) properties were identified in the AL fibers, and the studies about thermal using Thermo Gravimetric Analysis and Derivative Thermo Gravimetric analysis revealed that the maximum degradation temperature is 353.37 °C with kinetic activation energy of 89 kJ/mol. It is concluded from the result that the properties of ALFs guaranteed that it could be an alternative material as new reinforcement as green composites in the manufacturing and automobile industries.